Strengths and weaknesses of the algorithm based on multidimensional rainbow transformations and its ability to block attacks by third party channel - Harmash, D.V. (Radiotekhnika, 2021)
The paper considers the analysis of the essence and possibilities to protect the Rainbow post-quantum cryptographic algorithm. The main properties of algorithms based on multidimensional quadratic transformations are considered. Mathematical schemes and operations used by the Rainbow algorithm are given. The perspective of using algorithms based on multidimensional quadratic transformations in post-quantum time is estimated. An estimate of what resources and computing energy are required for the successful use of algorithms based on multidimensional quadratic transformations is given. The main positive aspects of the algorithm and its weaknesses are outlined. Analyzes are given regarding the ability of the algorithm to protect against attack by third-party channels.